Upaya Kepemimpinan Visioner Kepala Madrasah Lailiyah Ad-Diniyah Dalam Mengembangkan Mutu Pembelajaran Di Pondok Pesantren Al Hidayah Bumirejo, Kebumen - Al Mubarok, Akhmad Zidni; Faisal, Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The leadership of the head of the madrasah is one of those that affects the improvement of the quality of learning. the head of madrasah through visionary leadership is expected to be able to develop the quality of learning at Pondok Pesantren Al Hidayah Bumirejo, Kebumen. This study aims to identify the behavior of the head of madrasah in developing the quality of learning, especially visionary behavior in leadership. This study was conducted with a qualitative approach. The subjects of this study were head of madrasah lailiyah ad-diniyah, asatidz, and santri. data collection techniques from this study using the method of observation, interviews, and documentation. The results of this study show that, visionary leadership. This is evidenced from the results of research, namely: 1) formulate the vision of madrasah lailiyah ad-diniyah as a visionary leader; 2) socialize the vision to asatidz so that the vision is conveyed to the students; 3) implement the vision by looking at the quality of inputs, processes, and outputs.